Secure radio telemetry and data acquisition using wireless data communication system with portable UHF transceivers / Mohd Dani Baba and Deepak Kumar Ghodgaonkar - Baba, Mohd Dani; Ghodgaonkar, Deepak Kumar (2003)
Telemetry systems are an important part of communication and control technologies in today's industry. One of its main tasks is to acquire or collect data at remote location and send the data to a location either through cables or radio waves where the data can be received for evaluation and analysis. The main objective of this research is to design and develop a secure telemetry system that uses radio waves as a communication media to relay information for monitoring environmental conditions. The system comprises of two main subsystems; they are remote telemetry station (RTS) as a data collection center and base telemetry station (BTS) as a data evaluation center. The RTS comprises of a personal computer equipped with data acquisition system, voice band modem, analog transducers for measuring temperature, humidity and atmospheric pressure, and a portable UHF transceiver. On the other hand, BTS comprises of a personal computer equipped with data acquisition software, voice band modem and a portable UHF transceiver. A software programming based on LabVIEW was developed for data processing and presentation at both RTS and BTS. The data collected at RTS site are encrypted prior to transmission to the BTS by employing the One Time Pad (OTP) and Caesar Cipher algorithms. These algorithms are chosen because they are suitable for low bit rate data. The modems use frequency shift keying (FSK) modulation to convert digital signal into analog and vice versa. The modulated signal is transmitted from RTS to BTS by using the UHF transceiver with frequency modulation (FM) at 477.1 MHz as the carrier frequency. The data communication protocol used is serial asynchronous via RS232 port. The telemetry system is successfully designed and developed. The performance of the telemetry system is successfully evaluated in the laboratory and field for 1 km range. The results of the evaluation show that there is no bit error during 300 and 600 bps data rates and the average SNR is 28.96 dBm. The accuracy of data transmission is determined to be at 99.99%.